2012
DOI: 10.1021/jp209535p
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of Ethylene/Styrene Copolymers: Evidence of Sensitization of the Aromatic Moiety As Counterpart of the Radiation Protection Effect

Abstract: Molecules containing aromatics systems are more stable in the presence of ionizing radiations than alkanes. In the same way, introducing aromatic rings into aliphatic compounds increases their stability. The protective effect is nonlocal and likely results from the transfer of energy and species from the aliphatic moiety to the aromatic one. For years, it was commonly assumed that the aromatic moiety, which is very radiation resistant, accommodates the extra energy remaining unaffected. The use of Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This energy in aromatic molecules is then dissipated mainly by heat or light emission. 45 It was reported that, under γ-irradiation in polystyrene, the gaseous benzene yield is 8 × 10 −10 mol•J −1 . 46 The benzene yield we report here for the γ-irradiation of the Phen compound is the same within the error bars (10 −9 mol•J −1 , Table 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This energy in aromatic molecules is then dissipated mainly by heat or light emission. 45 It was reported that, under γ-irradiation in polystyrene, the gaseous benzene yield is 8 × 10 −10 mol•J −1 . 46 The benzene yield we report here for the γ-irradiation of the Phen compound is the same within the error bars (10 −9 mol•J −1 , Table 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The assumption we made that vinyl groups are created in the aliphatic moiety might be questioned. As we have already shown that the radiation protection effect conferred by the benzene rings is efficient but at its expense [12], it makes sense to analyze if vinyl formation comes, at least partially, from the destruction of the styrene units by energy transfers. Results obtained when irradiating polystyrene, PS, could give some insight on the chemical modifications presumably induced in the aromatic moiety of PES.…”
Section: Vinylsmentioning
confidence: 99%
“…Nevertheless, this protection effect is more efficient at RT, proving that the radical transfers play also a role. Finally, the aromatic moiety protects the aliphatic one, but at its expense since the aromatic moiety is consumed [12].…”
Section: Introductionmentioning
confidence: 99%
“…The overall hypothesis behind this work is that the lacquer studied herein will exhibit superior radiation resistance. This is substantiated by the fact that Toxicodendron succedanea contains hydroxyl phenyl groups that act as radical scavengers, enhancing radiation resistance via their ability to convert excitation energy into nonchemistry inducing energy in lacquer that has been cured . Further, Rogner and Langhals have shown via IR and mass spectroscopy that doses of 300 kGy (30 Mrad) electron beam (EB) do not result in measurable damage in qi‐lacquer (urushi) .…”
Section: Introductionmentioning
confidence: 99%